Epitaxial growth of semipolar InAlN films on yttria‐stabilized zirconia. Issue 10 (7th June 2017) - Oseki, Masaaki; Kobayashi, Atsushi; Ohta, Jitsuo; Oshima, Masaharu; Fujioka, Hiroshi
Abstract : We report on the epitaxial growth of semipolar InAlN (1 1 ¯ 03) on yttria‐stabilized zirconia (YSZ) by pulsed sputtering deposition (PSD). Unlike the direct growth of InAlN on YSZ that resulted in c ‐plane InAlN, the insertion of an InN buffer layer favored the growth of InAlN in the semipolar direction. Phase separation of semipolar InAlN taking place in the films with intermediate indium contents can be suppressed by low‐temperature (less than 400 °C) PSD growth. These semipolar InAlN films grown at low temperatures possessed sufficient optical quality to demonstrate photoluminescence at room temperature.